Management of Trauma Pain in the Emergency Medicine - V. J. Pikovskii; V. I. Barklaya; P. A. Davidov (Неотложная медицинская помощь)
The literature review is devoted to modern principles of acute pain management of traumatic genesis in the practice of emergency medical care. It describes the capability of pain intensity evaluation, and available methods of analgesia and pain relief medication. Special emphasis is laid on current data on inhaled methoxyflurane analgesia.